The Spillover Effect of a Flood on Pets and Their People: Implications for Rental Housing. Issue 3 (3rd July 2019) - Graham, Taryn M.; Rock, Melanie J.
ABSTRACT: When disasters strike, companion animals (pets) matter. Emergency planning for them is a key aspect of disaster preparedness, especially considering that people may delay evacuation out of concern for their pets. Temporary boarding options for pets are important; however, caregivers (owners) must ultimately return to permanent housing. Surprisingly little attention has been paid to housing recovery in the disaster literature on pet ownership, and no studies have examined the potential for increased vulnerability among tenants with pets. This study analyzed online rental listings in a city that was severely flooded in 2013. In the following year, demand for pet-friendly rental housing outweighed supply. Landlords frequently stipulated restrictions on the allowable sizes, species, or breeds of pets. Dogs were often banned outright. To keep their pets, prospective tenants needed to exercise flexibility in location and pay higher surcharges. The implications of housing insecurity for tenants with pets have broad relevance, not just in disaster circumstances. Giving up a companion animal to secure housing can negatively impact resilience, whereas living in unsafe environments to avoid pet relinquishment may increase vulnerability.